Resolving Phylogenetic Relationships Within the Trichophyton mentagrophytes Complex: A RADseq Genomic Approach Challenges Status of 'Terbinafine-Resistant' Trichophyton indotineae as Distinct Species - Švarcová, Michaela; Kolařík, Miroslav; Li, Yuanjie; Tsui, Clement Kin Ming; Hubka, Vít (Mycoses, 2025)
BACKGROUND: The Trichophyton mentagrophytes complex encompasses common dermatophytes causing superficial mycoses in humans and animals. The taxonomy of the complex is unstable, with conflicting views on the species status of some taxa, particularly T. indotineae and T. interdigitale. Due to the presence of intermediate genotypes, neither MALDI-TOF MS nor ITS rDNA sequencing can accurately distinguish all taxa in the complex, potentially contributing to clinical misdiagnoses. OBJECTIVES: This research resolves phylogenetic relationships within the T. mentagrophytes complex. Based on these data, the taxonomical recommendations are suggested. METHODS: In order to resolve the phylogenetic relationship of the T. mentagrophytes complex, we employed Restriction Site-Associated DNA Sequencing (RADseq) to produce a high-resolution single nucleotide polymorphism (SNP) dataset from 95 isolates. The SNP-based analyses indicated the presence of two major genetic clusters corresponding to T. mentagrophytes (including T. indotineae) and T. interdigitale. RESULTS: Our results challenge the species status of T. indotineae because of insufficient genetic divergence from T. mentagrophytes. Therefore, we propose designating T. indotineae as T. mentagrophytes var. indotineae (or T. mentagrophytes ITS genotype VIII) to avoid further splitting of the complex and taxonomic inflation. Although T. interdigitale shows clearer genetic differentiation, its separation is incomplete and identification of some isolates is ambiguous when using routine methods, leading us to consider it a variety as well: T. mentagrophytes var. interdigitale. CONCLUSIONS: We recommend using T. mentagrophytes as the overarching species name for all complex isolates. Where precise molecular identification is possible, the use of variety ranks is encouraged. Since identical resistance mechanisms are not specific to any genotype or dermatophyte species, identifying antifungal resistance is more important than differentiating closely related genotypes or populations.
Keywords: DNA fungální; Trichophyton mentagrophytes; DNA, Fungal; taxonomy; Polymorphism, Single Nucleotide; Humans; Phylogeny; Trichophyton interdigitale; antifungální látky; Sequence Analysis, DNA; anthropophilic dermatophytes; jednonukleotidový polymorfismus; genomika; antifungal resistance; zoophilic dermatophytes; Genotype; lidé; sekvenční analýza DNA; dermatophytosis; Arthrodermataceae; Antifungal Agents; fylogeneze; tinea; genotyp; Tinea; population structure; Genomics; Trichophyton